WAR NEWS IN THE PRESS OF THE 1920 IRAQI REVOLT - Hashem Hasan Al-tememy, Hashem Hasan Al-tememy (ALBAHITH ALALAMI, 2005)
Before introducing an accurate description of the publication of news about the Iraqi-British war in the press of the Great Iraqi revolution, it is necessary to note the importance of this research as it examines a remarkable phenomenon that lies at the heart of public attention at this particular time, where we live the repercussions of a new war similar, with some of its facts and activities, to the events of the Great Iraqi Revolution that broke out in many Iraqi cities. Therefore, the results of this research can be a starting point for new research characterization of the phenomenon of news coverage of war in the Iraqi press. The importance of research in the press of the Great Iraqi Revolution, according to the well-known researcher Dr. Kamal Mazhar, is reflected in its occupation of a distinguished history that needs to be studied and analyzed, in a manner that would help to better understand important aspects of one of the most important workshops of national liberation of the Iraqi people, especially with regard to the role of intellectuals. The "Revolution" and "Independence" newspapers are among the finest of the "The Great Iraqi Revolution" and form one of the most important contents of the Iraqi press. In addition, the list of original sources is indispensable for any historian who tackles the events of the revolution. The research will attempt to provide specific answers to three questions: First: Which newspapers represented the Great Iraqi Revolution in Iraq? Second: What is the nature of war news in those newspapers? Third: Who were the people who carried out the news coverage of the war? We must also refer to the definition of war correspondent and the importance of media war, which has a privileged position because it stands at the same level, with the military, political and economic forces to achieve victory, and therefore the military media is one of the pillars of military mobilization at the internal and external levels. Internally, media war mobilizes public opinion, raises morale and emphasizes the importance of its role in the battle and then prepares people to accept the complications of war, by clarifying its objectives and its motives, and create an atmosphere conducive to stability, reassurance, responsibility. In addition to creating contentment and activity between individual and public willingness, as well as, set up a loyal relationship between citizens and the country. Also, providing logical and convincing explanation when clarifying events and facts at the external level by addressing all political power centers through technical means of communication. During war, the importance of the war correspondent appears in providing the daily press with news and pictures from the front lines, in addition to criticism of hostile military plans and comment on the news, victories and defeats of the enemy in various quarters (1). Some describe the war correspondent as a delegate sent to the battlefield on a special mission during the war, and this task only appears in the case of war. This system isn’t followed by most of the newspapers, radio, television and cinema sometimes but during war, when the military affairs are the most important concerns of public opinion.